Roxanne [videorecording (DVD)]. - Martin, Steve, 1945-; Hannah, Daryl; Duvall, Shelley, 1949-; Rossovich, Rick. 1957-; Schepisi, Fred (Sony Pictures Home Entertainment, 2005)
C.D. Bales, a fireman with an astonishingly long nose, harbors a secret love for Roxanne, a beautiful astronomy student who is attracted to another man.